What Is the Association Between Physical Activity, Sedentary Lifestyle and Risk of Developing Cancer in the Adult Population? a Scoping Review [Cuál Es la Asociación Entre Actividad Física, Sedentarismo y Riesgo de Desarrollar Cáncer en Población Adulta? Una Revisión de la Literatura] - De Moraes-Ferrari, G (Sociedad Chilena de Nutricion Bromatologia y Toxilogica, 2021)
Regular physical activity (PA) has been associated with important metabolic benefits, as well as a decreased risk of developing some types of cancer. The objective of this scoping review is to synthesize the existing scientific evidence on the association of PA levels and the risk of developing cancer. This will allow a better orientation to future public policies aimed at increasing PA levels in the Chilean population. We searched for the latest global and national reports on PA and cancer as well as scientific databases (Pubmed, Web of Sciences, Scopus, Medline, Scielo and Google Scholar) using the following keywords: “exercise”, “neoplasms”, “cancer”, “colorectal”, “breast”, “endometrium”, “physical activity”, “exercise”, “sedentary lifestyle” and “sports”. Our review supports the protective association between PA and a lower risk of several cancers including colorectal, breast and endometrial cancer. However, more research is still needed to elucidate the role of PA on the risk for other common cancers. © 2021, Sociedad Chilena de Nutricion Bromatologia y Toxilogica. All rights reserved.